Patência a médio prazo de stenting venoso ilíaco para tratamento de síndrome pós-trombótico - Revisão Sistemática e Meta-análise - Adriana Machado Ferreira (2021)
INTRODUCTIONː Post-thrombotic syndrome (PTS) is the most common chronic complication of deep vein thrombosis. Recent studies suggested that iliac stenting in chronic obstructive venous disease is safe and effective. However, systematic reviews focusing on mid-term efficacy of iliac stenting in post-thrombotic syndrome are lacking. This systematic review aimed to analyse mid-term stent patency rates and clinical outcomes of iliac stenting in post-thrombotic syndrome. EVIDENCE ACQUISITIONː Two databases were searched: Pubmed/Medline and SCOPUS. Articles published between January 2000 and July 2020 were selected and titles and abstracts were independently reviewed. Eighteen articles were included for the qualitative analysis. From this initial set of articles, fourteen articles were included for the quantitative analysis. EVIDENCE SYNTHESISː Overall, 1008 patients were included in this study. The pooled technical success rate was 96%. The pooled primary and secondary patency rates were 98.2% and 100% at 30 days, 78.1% and 94.5% at 12 months and 66.3% and 89.4% at 36 months, respectively. The rates of ulcer healing, pain and edema relief were 78.1%, 53.4% and 48.8%, respectively. The pooled rate of complications including intraoperative venous injury, back pain and stent fracture were 28%, 57.1%, and 5.9%, respectively. CONCLUSIONSː Iliac venous stenting in PTS presents durable mid-term patency rates, as well as significant symptomatic improvement. Therefore, endovascular treatment should be considered in symptomatic patients with PTS.